Sweet bird of youth (1962) [videorecording (DVD)] - Brooks, Richard, 1912-1992; Newman, Paul, 1925-2008; Page, Geraldine; Knight, Shirley, 1936-2020-; Begley, Ed, 1901-1970; Torn, Rip, 1931-2019-; Williams, Tennessee, 1911-1983 (Archive collection., 2017)
A Hollywood gigolo, determined to become a star, teams up with Alexandra Del Lago, a washed-up Hollywood actress, on his way back to his small-town home.